The Relationship Between Tooth Brushing Methods and Gum Bleeding Among the Elderly at Posyandu Lansia in Surabaya - Dinda Alifiani Kunawi; Sunomo Hadi; Siti Fitria Ulfah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The elderly experience a decline in immune function, making them susceptible to dental and oral diseases, one of which is gum bleeding. Improper tooth brushing techniques can cause gum bleeding because brushing in the wrong direction can make the gums bleed easily and leave food residues uncleaned. Problem: The high percentage of gum bleeding during tooth brushing in the elderly at the Posyandu Lansia Kampung Mustika Baru Ngagel Surabaya in 2024. On average, the elderly have poor tooth brushing techniques. Objective: To analyze the relationship between tooth brushing methods and gum bleeding in the elderly at the Posyandu Lansia Kampung Mustika Baru Ngagel Surabaya in 2024. Research Method: This research is an analytical cross-sectional study. Sampling was done using purposive sampling with a sample of 36 elderly individuals. The data collection instruments used were observation sheets to measure tooth brushing methods and examination sheets to identify gum bleeding. The analysis technique used was the Chi-square test. Research Results: On average, the elderly's tooth brushing methods, after observation, were categorized as poor. There is a significant relationship between tooth brushing methods and gum bleeding in the elderly at the Posyandu Lansia Kampung Mustika Baru Ngagel Surabaya, with an asymp.sig (α) value of 0.000 (p < 0.05). Conclusion: The better the elderly brush their teeth, the less likely they are to experience gum bleeding, thereby reducing the risk of gum bleeding